A COMPARATIVE ANALYSIS DEFINITIONS OF ADMINISTRATIVE LAW - Bakaveckas, Audrius (European Scientific Journal, ESJ, 2014)
It must be stressed that currently there is no universally accepted definition of administrative law that would prevail in the theory of administrative law and have an equal meaning in different countries and different legal systems. This aspect encouraged the authors of the present article to carry out an in-depth review of the conceptions of administrative law found in literature on administrative law in various foreign countries. A comparative analysis of the definitions of administrative law was carried out in order to reveal the elements of their content that are used by different authors (scholars) to define administrative law as well as the similarities and differences of these definitions.